PROCESSING PALM FRONDS INTO CHARCOAL BRICKETS AS AN ALTERNATIVE FUEL IN TONDUHAN VILLAGE – SIMALUNGUN - Delyana Rahmawany Pulungan; Guntoro; Febriana Roosmawati; Adi Widjajanto; Yosua Purba; Purnama Fatur Arivai; Safira Anandra Meliala; Suci Madani Harahap; Ragil Satrianto; Dimas Prasetyo (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2023)
Oil palm frond waste is often ignored in Tonduhan Village, Simalungun Regency. These oil palm fronds are often left to dry by village communities without optimal use. So, through this community service, students and ITSI lecturers provide education regarding handling palm oil waste in an environmentally friendly manner and even with high economic value, namely processing palm fronds into charcoal briquettes that can be used for themselves and sold to increase the village community's income. The activity began by introducing the potential of palm oil and its waste which provide benefits and economic value. Then the community was invited to take part in making charcoal briquettes from palm frond waste. The village community was very enthusiastic in this activity. Their knowledge increases in processing frond waste and is very active in this activity.